2019
DOI: 10.1007/s00394-019-01930-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of out-of-season orange modulates fat accumulation, morphology and gene expression in the adipose tissue of Fischer 344 rats

Abstract: Purpose According to the xenohormesis theory, animals receive signals from plants that give clues about the changing environment, and thus, depending on the season of the year, animals develop physiological changes to adapt in advance to the seasonal changes. Our objective was to study how the same fruit cultivated during two different seasons could affect the adipose tissue of rats. Methods Thirty-six Fischer 344 rats were acclimated for 4 weeks to long-day or short-day (SD) photoperiods. After adaptation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
(71 reference statements)
0
14
1
Order By: Relevance
“…For histological analyses, frozen IWAT samples were thawed and fixed in 4% formaldehyde and processed as explained previously [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For histological analyses, frozen IWAT samples were thawed and fixed in 4% formaldehyde and processed as explained previously [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The area and number of adipocytes were measured using the open source software Adiposoft (CIMA, University of Navarra, Spain). Four fields per sample and six samples from each group were measured, and the area, total adipocyte number, and adipocyte size frequencies were calculated as explained previously [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the out-of-season consumption of navelina oranges ( Citrus x sinsensis ) for ten weeks in the same animal model also exerted deleterious effects induced by an obesogenic diet, such as dyslipidemia and insulin resistance, increasing fatty acid synthesis in white adipose tissue and downregulating lipid uptake and β-oxidation in brown adipose tissue [119].…”
Section: Mechanisms Implicated In the Modulation Of Metabolism By mentioning
confidence: 99%
“…Therefore, the physiological and molecular changes elicited by seasonal fruit consumption could be partially explained by the modulation of the mammalian clock system. In fact, the consumption of both Prunus avium L. and Citrus x sinsensis has been correlated with the modulation of mRNA levels of different peripheral clock-related genes such as Nr1d1 in skeletal muscle and Per2 and Cry1 in the liver and white adipose tissue of healthy rats when they are consumed out of season [116,117,119]. In accordance, previous studies performed by our group have demonstrated that grape seed proanthocyanidins (PAs), a subclass of flavonoids with a marked protective effect against diet-induced dyslipidemia and insulin resistance [94], could significantly modulate both central and peripheral biological rhythms in male Wistar rats.…”
Section: Mechanisms Implicated In the Modulation Of Metabolism By mentioning
confidence: 99%